AgxH3−xPMo12O40/Ag nanorods/g-C3N4 1D/2D Z-scheme heterojunction for highly efficient visible-light photocatalysis. Issue 19 (17th April 2019) - Zhao, Xinyu; Zhang, Yi; Zhao, Yingnan; Tan, Huaqiao; Zhao, Zhao; Shi, Hongfei; Wang, Enbo; Li, Yangguang
Abstract : Synergism of light absorption, 1D/2D structure, good interface contact, and Z-scheme endowed the Ag x H3− x PMo12 O40 /Ag/C3 N4 composite with excellent performance. Abstract : Reasonably designing Z-scheme photocatalysts has been deemed to be an ideal and prospective way to develop new and highly efficient photocatalytic materials for removing environmental pollutants. Herein, a new type of Ag x H3− x PMo12 O40 /Ag nanorods/g-C3 N4 1D/2D Z-scheme photocatalyst ( abbr. APM/C3 N4 ) was fabricated by a simple self-assembly procedure. Transmission electron microscopy (TEM) images revealed that the 1D silver polyoxometalate (POM) nanorods loaded with Ag nanoparticles (Ag x H3− x PMo12 O40 /Ag = APM) were well dispersed on the plicated 2D g-C3 N4 nanosheets. Photocatalytic experiments demonstrated that these composite catalysts exhibited an excellent and durable photocatalytic performance for the degradation of methyl orange (MO) and tetracycline (TC) and the photoreduction of Cr(vi ) under visible light, which was significantly higher than that of the individual components and most of the previous reported materials. The photocatalytic mechanism suggests that superoxide and holes are the main active species in MO photodegradation, demonstrating its Z-scheme photocatalytic process. The synergistic effects of the enhanced light absorption, unique 1D/2D hybrid heterojunction structure, good and efficient interfacial contact and Z-scheme process endowed the as-prepared APM/C3 N4 composites with excellent performance. This study may provide a new comprehension into the design of polyoxometalate-based Z-scheme hybrid materials for photocatalytic applications in the removal of organic and inorganic pollutants from wastewater.